Financial Literacy, Behavioral Biases and Stock Investment Decisions among College Students - Libi, Sujit Kumar; Sapkota, Mohan Prasad; Poudel, Jyoti (BIC Journal of Management, 2025)
This study examines the influence of financial literacy and behavioral biases on stock investment decisions among Nepalese college students. It used a quantitative research approach, focusing on students from four major universities in Bagmati Province, with a total population of 268,838. It distributed 200 questionnaires by utilizing purposive sampling techniques to the university level who are currently studying. However, only 117 responses were utilized after screening incomplete and unnecessary responses. Questionnaires were developed using 5- point Likert type, closed end, structured questionnaires. This study employed descriptive statistics, correlation analysis, and multiple regression. The result shows that financial literacy, prospects biases and heuristic biases play a significant positive contribution to investment decisions. Among them, financial literacy plays the most key role in guiding rational investment decisions. However, investment decisions are positively impacted by herding behavior, but coefficient is insignificant. Hence, this study found that financial literacy and behavioral biases have significant positive contributions on irrational investment decisions. Finally, this study concluded that behavioral biases lead to investment mistakes, so the course of behavioral finance needs to be incorporated into financial education programs. Such programs should aim to strengthen students’ decision-making abilities through practical tools like stock market simulations and bias-awareness training. Overall, the study offers useful information for educators and policymakers to better support young investors and encourages further investigation into cultural and long-term behavioral factors.